TOXICOLOGICAL AND BEHAVIOR ANALYSES OF A FOLIOSE LICHEN PARMOTREMA TINCTORUM (DELISE EX NYL.) HALE EXTRACT USING ZEBRAFISH (DANIO RERIO) MODEL - SHENBAGAM, MUTHU; MARIRAJ, MURUGAN; KALIDOSS, RAJENDRAN; ARUMUGAM DEEPA, MACHAMPALAYAM; PONMURUGAN, PONNUSAMY (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The objective of the study was to evaluate the toxicity and behavior analysis with the extract of foliose lichen Parmotrema tinctorum against the adult zebrafish. Methods: The zebrafishes were exposed to different concentrations of P. tinctorum extract such as 50, 100, and 200 mg/ml for 7 days of exposure, in which the mortality and behavioral responses of zebrafishes were recorded. The standard histopathological examination was conducted with the lichen extracts of P. tinctorum. Results: The results revealed that P. tinctorum extract did not show any prominent behavior abnormalities in zebrafishes even at a high concentration of 200 mg/ml. The extract was found to have dose-dependent toxic to zebrafish and the number of neutrophil cells in the muscle bundles reduced at a high concentration. The results of the inflammatory marker gene expression using polymerase chain reaction results suggested that the dose-dependent suppression of tumor necrosis factor gene by the P. tinctorum lichen extract. Conclusion: Overall, concluded that the extract might contain anti-inflammatory induction properties and further tests are required to prove apoptosis and anticancer activity using other in vivo or in vitro techniques.